Degrowth – Utopia or Reality? - Buraj, Ivan (Studia Philosophiae Christianae, 2024)
The main goal of the following article is to present and justify the philosophical concept of degrowth as a real alternative to the cult of (unlimited economic) growth, the driving force of which is the pursuit of profit, which devastates the individual and the entire society, and last but not least, nature and the climate. It is also critical of today’s generally recognized options for solving the climate crisis, such as the strategy of the so-called sustainable development or green growth, which – as the author shows with several examples – may indeed help to solve it, but they do not consistently solve it. Such a permanent solution must involve a total and radical change in the way of life, which, would limit people, but would also be attractive enough for them. Although the focus is on a philosophical analysis of the whole issue, the author considers its historical, sociological and political aspects as well, to avoid excessive generalities and at the same time keep its philosophical breadth and depth. ---------------------------------------- Received: 19/06/2024. Reviewed: 3/10/2024. Accepted: 5/11/2024.